An Ontology of the Submarine Relief for Analysis and Representation on Nautical Charts. (February 2015) - Yan, Jingya; Guilbert, Eric; Saux, Eric
<x content-type="archive" xml:space="preserve">Abstract</x> A nautical chart is a kind of map used to describe the seafloor morphology and shoreline of adjacent lands. One of its main purposes is to guarantee safety of navigation. As a consequence, the construction of a nautical chart follows very specific rules. The cartographer has to select and highlight undersea features according to their relevance to navigation. In an automated process, the system must be able to identify and classify these features from the terrain model. This paper aims therefore to define ontologies of the submarine relief and nautical chart that will be at the root of a model-oriented generalization process. To the best of our knowledge, no ontology has been defined to formalize the geographical and cartographic objects for nautical chart representation. Thus, a bottom-up approach was developed to extract and model knowledge derived from standards established by the International Hydrographic Organization (IHO) and cartographers' expertise. The submarine relief ontology formalizes undersea features describing the submarine relief. Four concepts (composition, morphometric class, shape value and depth value) are introduced to describe properties and relationships between undersea features. The cartographic representation ontology of nautical charts will define several concepts (chart, features, isobathymetric lines and soundings) for the representation of undersea features on the chart.